HLA-DPB1 and HLA-C alleles are associated with leprosy in a Brazilian population - Covolo de Souza-Santana, Fabiana; Querino, Gislaine Aparecida [UNESP]; Mendes Camargo, Rodrigo [UNESP]; Nieto Brito de Souza, Vânia [UNESP]; Bettoni Ballallai Mangilli, Priscila; Távora Mira, Marcelo; Cavalcanti Bezerra, Ohanna; Kehdy, Fernanda; Laguila Visentainer, Jeane Eliete; Alves, Hugo Vicentin; Jarduli, Luciana Ribeiro; Ozório Moraes, Milton; et al. (Elsevier, 2021)
Despite intense efforts, the number of new cases of leprosy has remained significantly high over the past 20 years. Host genetic background is strongly linked to the pathogenesis of this disease, which is caused by Mycobacterium leprae (M. leprae), and there is a consensus that the most significant genetic association with leprosy is attributed to the major histocompatibility complex (MHC). Here, we investigated the association of human leukocyte antigen (HLA) class I and II genes with leprosy in a Brazilian population encompassing 826 individuals from a hyperendemic area of Brazil; HLA typing of class I (-A, -B, -C) and class II (-DRB1, -DQA1, -DQB1, -DPA1, and -DPB1) loci was conducted. Initially, the associations were tested using the chi-square test, with p-values adjusted using the false discovery rate (FDR) method. Next, statistically significant signals of the associations were submitted to logistic regression analyses to adjust for sex and molecular ancestry data. The results showed that HLA-C*08, -DPB1*04, and -DPB1*18 were associated with protective effects, while HLA-C*12 and -DPB1*105 were associated with susceptibility to leprosy. Thus, our findings reveal new associations between leprosy and the HLA-DPB1 locus and confirm previous associations between the HLA-C locus and leprosy.
Keywords: Genetic susceptibility; HLA; Leprosy; Mycobacterium leprae